1989
DOI: 10.1111/j.1526-4610.1989.hed22904246.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium‐Induced Headache

Abstract: A 23-year old woman developed headache and papilledema due to benign intracranial hypertension (BIH) while taking lithium carbonate for only seven months because of manic-depressive disease. Having discarded other causes, drug ingestion was the most likely etiology of the syndrome since it was observed that symptoms improved upon lithium withdrawal and worsened when the treatment was restarted. This report shows that BIH may appear as a side-effect of relatively short-term therapy with lithium and, therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Commonly accepted medications include the cycline class of antibiotics (minocycline, tetracycline), lithium, and growth hormone. [5][6][7][8][9][10] Adults with primary intracranial hypertension presenting with optic nerve edema but without headache, essentially asymptomatic or nearly asymptomatic individuals, are well described. [10][11][12][13] Published reports of adult patients suggest that 9% to 38% of patients have optic nerve edema only without headache and this largely depends on the population size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly accepted medications include the cycline class of antibiotics (minocycline, tetracycline), lithium, and growth hormone. [5][6][7][8][9][10] Adults with primary intracranial hypertension presenting with optic nerve edema but without headache, essentially asymptomatic or nearly asymptomatic individuals, are well described. [10][11][12][13] Published reports of adult patients suggest that 9% to 38% of patients have optic nerve edema only without headache and this largely depends on the population size.…”
mentioning
confidence: 99%
“…Commonly accepted medications include the cycline class of antibiotics (minocycline, tetracycline), lithium, and growth hormone. 5 –10…”
mentioning
confidence: 99%
“…If undetected, this syndrome can lead to blindness. There are 7 cases of lithium-induced benign intracranial hypertension in the adult psychiatric literature (Levine and Puchalski 1990, Alvarez-Cermeno et al 1989, D'Anglejan-Chatillon et al 1989, Saul et al 1985, Pesando et al 1980, Lobo et al 1978 and at least 30 cases reported in the medical literature (Fraunfelder et al 1992), but no previously reported cases in children. We report a case of a child who was diagnosed with benign intracranial hypertension following 11 weeks of treatment with lithium.…”
mentioning
confidence: 96%